Desenvolvimento de Magnésia Cáustica para Revestimento de Aço Elétrico - Almeida, Felipe Bento (Universidade Federal de São Carlos, 2021)
Electric steels are ferrous alloys with up to 3.5 wt.% Silicon in its composition, and with carbon concentrations around 20 ppm. They are materials with excellent magnetic properties, generally used in the manufacture of transformer cores, small and large electric motors and electricity meters. During its processing, electric steel is rolled into slab shape. Then, the material is subjected to a heat treatment in which the carbon inside it, initially at concentrations around 0.2% by mass, is extracted. Also, in this stage, a vitreous silica layer is formed on the surface of the sheets. Then, the material is coated with a suspension of caustic magnesia, and sent to a final annealing, in which the magnesia reacts with the silica layer previously formed, producing a forsterite film on the surface of the steel sheets. This film performs several important functions in the final product. For the formed forsterite film to have the appropriate characteristics for the application, the caustic magnesia used must have a series of properties in specific ranges. In the present work, it was verified what are the properties and the ranges of properties that a caustic magnesia must have to be used in this application. We also sought to produce a caustic magnesia with all these properties from products of the refractory company RHI Magnesita. In addition, we tried to test the developed products in electric steel manufacturers, to verify the possibility of starting a supply of the material to these manufacturers.
Development of Caustic Magnesia for Electric Steel Coating
Keywords: Aço elétrico. Aço silício. Revestimento. Óxido de Magnésio. Magnésia Cáustica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS